Gene flow in the Antarctic bivalve Aequiyoldia eightsii (Jay, 1839) suggests a role for the Antarctic Peninsula Coastal Current in larval dispersal. Issue 9 (16th September 2020) - Muñoz-Ramírez, Carlos P.; Barnes, David K. A.; Cárdenas, Leyla; Meredith, Michael P.; Morley, Simon A.; Roman-Gonzalez, Alejandro; Sands, Chester J.; Scourse, James; Brante, Antonio
Abstract : The Antarctic Circumpolar Current (ACC) dominates the open-ocean circulation of the Southern Ocean, and both isolates and connects the Southern Ocean biodiversity. However, the impact on biological processes of other Southern Ocean currents is less clear. Adjacent to the West Antarctic Peninsula (WAP), the ACC flows offshore in a northeastward direction, whereas the Antarctic Peninsula Coastal Current (APCC) follows a complex circulation pattern along the coast, with topographically influenced deflections depending on the area. Using genomic data, we estimated genetic structure and migration rates between populations of the benthic bivalve Aequiyoldia eightsii from the shallows of southern South America and the WAP to test the role of the ACC and the APCC in its dispersal. We found strong genetic structure across the ACC (between southern South America and Antarctica) and moderate structure between populations of the WAP. Migration rates along the WAP were consistent with the APCC being important for species dispersal. Along with supporting current knowledge about ocean circulation models at the WAP, migration from the tip of the Antarctic Peninsula to the Bellingshausen Sea highlights the complexities of Southern Ocean circulation. This study provides novel biological evidence of a role of the APCC as a driver of species dispersal and highlights the power of genomic data for aiding in the understanding of the influence of complex oceanographic processes in shaping the population structure of marine species.